Somatic and psychiatric symptoms of brain tumors - a review of the literature - Joanna Olszak; Karolina Zalewa; Dominika Orłowska; Lidia Bartoszek; Wojciech Kapłan; Karol Poleszczuk; Mikołaj Poleszczuk; Alicja Milewska; Anna Czuba (Journal of Education, Health and Sport)
Introduction and Purpose